Nitrate monitoring in oil palm drainages (Elaeis guineensis): A tool for crop sustainability (UNED Research Journal, 2020)
Introduction: Most nitrogen added in fertilizers to oil palm plantations (Elaeis guineensis) is lost by storm drainage or nitrate leaching, which impacts receiving water bodies and associated ecosystems. Losses could affect the sustainable development of the activity. Objective: This work evaluates the nitrates monitoring in agricultural drains of an oil palm crop, as a tool for decision making of fertilizer application and loss reduction. Methodology: We analyzed the concentration of nitrates in four drains located in soil with palm cultivation of different textural class, and homogeneous conditions of plantation age, climate and fertilization type, before and after fertilization events. We estimated the nitrate load, QNO3- (mg s-1), statistical and trend differences in drainages. Results: QNO3- increases after fertilization, nevertheless, there is a significant difference in the in the variance of the groups (0.000033, alpha = 0.05) determined by the variation of QNO3- of the drainage located in soil of clay textural class (Q4). The QNO3- exhibits a more positive rate followed of a more negative decrease after fertilization in Q4 than in the drainage of sandy textural class. Discussion: The differences of QNO3- in the drainages are related to the textural class of the drained soil, the development of the roots and the depth at which the washing, assimilation, leaching and nitrate processing processes occur. Conclusion: The monitoring of nitrates in the drains of this crop allows to estimate the tendency of QNO3- related to the textural class of the soil, and to visualize the rate of losses by leaching or pluvial washing. We recommend monitoring of QNO3-in oil palm drains to make decisions about reduced or delayed fertilizer application in order to reduce losses.
Keywords: palm oil; fertilization; nitrates; sustainable agriculture; precision agriculture; natural resources